2019
DOI: 10.1093/jas/skz159
|View full text |Cite
|
Sign up to set email alerts
|

BEEF SPECIES–RUMINANT NUTRITION CACTUS BEEF SYMPOSIUM: Energy and roughage levels in cattle receiving diets and impacts on health, performance, and immune responses1

Abstract: Transition of newly received feedlot cattle from a forage- to grain-based diet is challenging, and the appropriate roughage level in receiving diets is debatable. Nutritionists must consider the paradox of dietary transition and roughage level to mitigate ruminal acidosis, yet concomitantly low feed intake presents difficulty in achieving nutrient requirements when metabolic demand is increased due to inherent stress and disease challenge during the receiving period. Previous research suggests that performance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 34 publications
0
22
0
Order By: Relevance
“…Dry matter intake is characteristically low within the first 2 wk of feedlot arrival and is coupled with immunosuppression and negative energy balance induced by traditional beef marketing channels ( Nagaraja et al, 1998 , Richeson et al, 2019 ). Sowell et al (1999) observed that steers diagnosed with BRD spent 30% less time eating than healthy cohorts, especially within the 4-d following feedlot arrival.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Dry matter intake is characteristically low within the first 2 wk of feedlot arrival and is coupled with immunosuppression and negative energy balance induced by traditional beef marketing channels ( Nagaraja et al, 1998 , Richeson et al, 2019 ). Sowell et al (1999) observed that steers diagnosed with BRD spent 30% less time eating than healthy cohorts, especially within the 4-d following feedlot arrival.…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, cattle experience immunosuppression and a negative energy balance upon feedlot arrival. Feed intake is concomitantly low during this time, averaging 1.5% of body weight (BW) in the first 2 wk following arrival, which further exacerbates immunosuppression due to inadequate nutrient intake ( Nagaraja et al, 1998 ; Richeson et al, 2019 ). As observed by Sowell et al (1998) , steers diagnosed with BRD spent 30% less time at the feed bunk than healthy cohorts, with differences in dry matter intake (DMI) being most pronounced within the initial 4 d following arrival ( Sowell et al, 1998 , 1999 ).…”
Section: Introductionmentioning
confidence: 99%
“…This is likely a defense mechanism, as the overall function is to reserve plasma glucose for maximal brain function during a stress event by promoting gluconeogenesis but reducing glucose utilization by skeletal muscle and white adipose tissue ( Kuo et al, 2015 ). Marketing, transportation, and feedlot arrival of high-risk cattle is a stressful event ( Richeson et al, 2019 ), and the stress-induced production of glucocorticoid and subsequent increase in total white blood cell count supports the observed decrease in treatment for BRD in CHR-fed cattle ( Smock et al, 2020 ). Furthermore, CHR did not influence receiving period performance but did decrease performance during the finishing period ( Smock et al, 2020 ).…”
Section: Resultsmentioning
confidence: 93%
“…As a result of limited or no feed and water access and inflammation during marketing and transportation, high-risk cattle arrive at the feedlot in a catabolic and chronically stressed state ( Richeson et al, 2019 ). The observed serum chemistry day effects ( Table 1 ) clearly indicate the metabolic disruption high-risk cattle possess at feedlot arrival and how they return to homeostasis later in the receiving period.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation